2009
DOI: 10.14430/arctic197
|View full text |Cite
|
Sign up to set email alerts
|

Response of Overwintering Caribou to Burned Habitat in Northwest Alaska

Abstract: Caribou (Rangifer tarandus granti) use lichens, when available, as primary forage on their winter range. In boreal forest habitats, wildland fires effectively destroy lichens, and overwintering caribou are known to avoid burned areas for decades while lichen communities regenerate. However, little has been published about caribou response to burned habitat in tundra ecosystems. To assess the relationship between winter caribou distribution and burned areas, we instrumented Western Arctic Herd caribou with sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 54 publications
8
60
0
Order By: Relevance
“…This result may seem intuitive as caribou tend to avoid habitat that has recently burned (Joly et al, 2007a;Joly et al, 2010), whereas moose select for it (Maier et al, 2005). Furthermore, high moose densities could sup¬ port high wolf densities which would reduce its suit¬ ability for caribou (Bergerud, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result may seem intuitive as caribou tend to avoid habitat that has recently burned (Joly et al, 2007a;Joly et al, 2010), whereas moose select for it (Maier et al, 2005). Furthermore, high moose densities could sup¬ port high wolf densities which would reduce its suit¬ ability for caribou (Bergerud, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Caribou can be found throughout their annual range during winter, though use is more concentrated on the Nulato Hills, upper Kobuk River and eastern Seward Peninsula (Joly et al, 2007a). These regions are diverse, with extensive areas of treeless tussock tundra (Eriophorum vaginatum, Carex spp.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Following a major disturbance such as fire or heavy grazing pressure, the recovery of lichen mats may take a lengthy period of time (~45 kg ha" yr" , Auclair 1985) preventing their use by caribou for up to 50 years (Scotter 1964, Kelsall 1968, Klein 1982, Joly et al 2003, 2007a, Jandt et al 2008.…”
Section: Chapter -Thesis Introduction Contextmentioning
confidence: 99%
“…Although researchers have noted that caribou sometimes forage in recently burned habitats Rowe 1975, Joly et al 2003), they are mostly observed to avoid these areas in favour of older, lichen-rich communities (>55 years of age; Klein 1982, Thomas et al 1996, Joly et al 2003, 2009a. Lichen species preferred by caribou (e.g., Cladina rangiferina, C mitis) are associated with late-successional serai stages in boreal forests (Maikawa and Kershaw 1976), and in the short term are lost following fire (Klein 1982, Thomas et al 1996Joly 2003Joly , 2007aJoly , 2009a.…”
Section: Chapter -Thesis Introduction Contextmentioning
confidence: 99%